2020
DOI: 10.1111/codi.15444
|View full text |Cite
|
Sign up to set email alerts
|

Variation in rectoanal inhibitory reflex after laparoscopic intersphincteric resection for ultralow rectal cancer

Abstract: Aim The aim was to evaluate the physiological variation in rectoanal inhibitory reflex (RAIR) after laparoscopic intersphincteric resection (Lap‐ISR) for ultralow rectal cancer. Method This was a retrospective study that included 56 patients who underwent Lap‐ISR from a prospectively collected database. The RAIR was examined preoperatively and up to 12 months after ileostomy closure. The primary outcome included physiological variation in RAIR and its difference between partial, subtotal and total ISR. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The FIQL was adopted in this study in that it has a potentially higher sensitivity in monitoring QoL changes after ISR than health-related QoL questionnaires, as we reported more recently. 6 Our data showed significant improvements in domains of lifestyle and coping/ behavior, yielding an overall recovery of FIQL after ISR. Interestingly, the FIQL was strongly correlated with the Delphi consensus severity score but was weakly or moderately associated with the WIS and the LARS score.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The FIQL was adopted in this study in that it has a potentially higher sensitivity in monitoring QoL changes after ISR than health-related QoL questionnaires, as we reported more recently. 6 Our data showed significant improvements in domains of lifestyle and coping/ behavior, yielding an overall recovery of FIQL after ISR. Interestingly, the FIQL was strongly correlated with the Delphi consensus severity score but was weakly or moderately associated with the WIS and the LARS score.…”
Section: Discussionsupporting
confidence: 52%
“…[2][3][4] However, in terms of functional concerns, low anterior resection syndrome (LARS) development is virtually inevitable after ISR because of a multiple surgery-and patient-related factors. [5][6][7][8][9] The LARS score and the Wexner incontinence score (WIS) are frequently adopted as patient-reported outcome measures to evaluate bowel dysfunction after rectal surgery. Although both are quick evaluation tools, the former underestimates the impact of evacuatory dysfunction, and the latter focuses only on fecal incontinence.…”
Section: Medidas Principales De Resultadomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incidence of total complications increased. The incidence of total complications, containing bleeding, incisional hernia, abscesses, etc., may increase due to the surgery of both resection and stoma [50][51][52][53][54]. It should be noted that among 17 studies on postoperative complications included in this study, there were only 3 randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Previous studies have indicated that a high prevalence (60%–90%) of LARS maintains a long-term negative impact on QoL after LAR. 11 As far as ISR is concerned, it seems that LARS is an inevitable complication because of resection of the internal anal sphincter, 2 removal of the anal transition zone, 9 loss of the rectoanal inhibitory reflex, 12 and creation of a temporary diverting stoma, 11 all of which are considerable contributing factors for this complex syndrome. It is important to note that patients undergoing ISR report significantly worse incontinence symptoms than patients undergoing traditional LAR, 11 whereas the QoL outcomes remain controversial.…”
mentioning
confidence: 99%